2021
DOI: 10.1111/twec.13212
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effects of openness on real and nominal effective exchange rates in emerging and developing economies

Abstract: Studying the determinants of exchange rates is important for understanding economic development, trade patterns, investment decisions and for recommending economic policies. Trade openness is one of the important factors that affect exchange rates. With increase in globalisation, economies around the world are more integrated through liberalised foreign trade policies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In other words, the more liberalized a country’s capital account is, the less the pressure global shocks would impose on the foreign exchange rates. Besides, Keefe and Saha ( 2022 ) show financial openness–proxied by the KOF globalization index–can partially absorb the impact of domestic shocks, such as shocks to inflation, interest rate differentials, and government debt. Their threshold model regressions reveal that in less open economies, macro variables elicit larger responses in the real exchange rates; in highly open economies, such responses are negligible, if not nonexistent.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…In other words, the more liberalized a country’s capital account is, the less the pressure global shocks would impose on the foreign exchange rates. Besides, Keefe and Saha ( 2022 ) show financial openness–proxied by the KOF globalization index–can partially absorb the impact of domestic shocks, such as shocks to inflation, interest rate differentials, and government debt. Their threshold model regressions reveal that in less open economies, macro variables elicit larger responses in the real exchange rates; in highly open economies, such responses are negligible, if not nonexistent.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…The authors found particularly trade openness to be connected with economic growth and exchange rates. In a related study the direct and indirect effects of the degree of openness in emerging and developing economies on exchange rate movements are shown by Keefe and Saha (2022). Another factor is revealed by the study Chen et al (2020), where the authors determined the impact of economic policy uncertainty on exchange rates.…”
Section: Introductionmentioning
confidence: 95%